PENGARUH DOUBLE ACTION KOMPRES HANGAT CITRUS AURANTIFOLIA TERHADAP NYERI REUMATHOID ARTRITIS PADA LANSIA DI WILAYAH KERJA PUSKESMAS Tg.SENGKUANG KOTA BATAM - Siska, Dedy; Dharma Yudastoro, Fasida; Ayu Suntara, Ditte (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Rheumatoid Arthritis is a condition where the immune system attacks itself, causing inflammation and causing pain. One of the pain relievers for rheumatoid arthritis is a warm compress from Citrus aurantifolia which allows the absorption of the substances naringenin and hesperidine to suppress the production of prostaglandines which trigger pain. This study aims to determine the effect of double action Citrus aurantifolia warm compresses on Rheumatoid Arthritis pain with a pre-experimental design. The number of elderly in this study was 10 elderly with purposive sampling. The research results were obtained before the pretest on day 1 of the elderly who experienced controlled severe pain, 20%, and after the posttest on day V, not a single elderly person experienced controlled severe pain. The results of the Marginal Homogeneity statistical test for the pain intensity variable and the Citrus aurantifolia warm compress variable showed that there was a significant difference in the pain scale between before and after the Citrus aurantifolia warm compress (p –value= 0.012 with α <0.05).Keywords: Rheumatoid Arthritis, warm compress Citrus aurantifolia, pain, Elderly, analytical observation